Sustainable small ruminant breeding program for climate-smart villages in Kenya - Ojango, Julie M.K.; Audho, James O.; Oyieng, Edwin P.; Recha, John W.M.; Muigai, Anne W.T. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Improving productivity of sheep and goats (i.e. small ruminants- SR) under smallholder farming systems faced with challenges of unfavourable climatic events has been identified as one means of enhancing livelihoods of communities living in these areas. Interventions are targeted through clusters of farmers grouped into “climate smart villages” (CSV) under a collaborative action by CCAFS, ViAgroforestry, World Neighbours and the Kenya Agricultural and Livestock Research Organization. This baseline study was implemented to understand the socio-economic aspects, population structure, management practices and production constraints of SR in the CSV of the Lower Nyando basin of Kenya. The results indicate that the community is mainly comprised of young people (mainly students) and men and women above 50 years of age who manage the various households. Land sizes owned are small, with 58% of the households owning less than one hectare of land on which they grow crops and rear on average eight SR in addition to some cattle and poultry. The SR reared are mainly indigenous breeds, with some crossbreds resulting from the few introduced Red Maasai sheep and the Galla goats for improved productivity. Breeding of SR is not controlled, and since larger animals fetch better prices on the market, over time negative selection has affected the SR population. SR are generally left to graze on stovers from crops, and take a long time to grow to maturity (up to 4 years). Farmers in the CSV know what traits they desire in their SR, and are willing to learn and change their practices in order to improve their livelihoods. It is evident that the organization of the households into CSVs provides a great opportunity for capacity development which should have a strong component of engaging the youth, and the development of a selection and breed improvement program for SR in the Lower Nyando area.